Sociodemographic Correlates and Symptoms of Depression, Anxiety and Stress among a Sample of Nigerian Medical Students - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Introduction:Previous studies have shown that medical students globally experience various degrees of psychopathologies such as depression, anxiety, and stress while in medical school.Objective:This study aimed at assessing the symptoms of depression, anxiety, and stress in a sample of Nigerian medical students.Materials and Methods:A cross-sectional and descriptive design was adopted for this study. A total of 240 medical students from the second to sixth years studying at the Lagos State University College of Medicine, Lagos, Nigeria were invited to participate in the study. They completed a proforma form that collected their sociodemographic variables and short version of the Depression Anxiety and Stress Scale.Results:A total of 240 medical students participated in the study. The age range was between 25 and 34 years, (mean 25 years; SD = 4.5); 120 (50%) were females and only 9 (3.75%) were married while a large majority of the participants 229 (95.4%) were single. A small number of the participants 9 (3.8%) and 34 (14.2%) smoked cigarettes and consumed alcohol, respectively. The DASS analysis showed that 15 (6.3%), 23 (9.5%), and 148 (61.6%) experienced symptoms of depression, anxiety, and stress, respectively.Conclusion:The study demonstrated that Nigerian medical students also manifested with various symptoms of psychopathology. Nigerian medical students should be taught stress and change management strategies to assist them to cope with the stressful nature of medical training.